Group Psychotherapy With Fibromyalgia Patients: A Systematic Review - Esin TEMELOĞLU ŞEN; Ayla HOCAOĞLU; Özlem SERTEL BERK (Archives of Rheumatology, 2019)
Objectives: This review aims to investigate the factors that play a role on the efficacy of group psychotherapy (GP) interventions for fibromyalgia syndrome (FMS). Materials and methods: We employed a search using keywords group psychotherapy and fibromyalgia in the databases of Scopus, Web of Sciences, CINAHL, BMJ, MEDLINE, ScienceDirect and EBSCOhost. Results: A total of 30 original studies were identified. These studies, which aimed to improve primary outcomes (POs-pain and fibromyalgia impact) and/or secondary outcomes (SOs-psychosocial), indicated that 15 were conducted in a multidisciplinary (MT) fashion, and the rest were unidimensional as they employed only GPs. Cognitive behavior therapy, which modifies dysfunctional thoughts and accompanying behaviors, was the most utilized psychological intervention. Overall, MTs were only slightly superior to GPs; however, improvements in POs were more frequent than SOs in MTs, and the vice versa in GPs. Conclusion: Although studies varied in various methodological characteristics, the content of the interventions in MTs should be designed to cover the biopsychosocial nature of FMS.